Financial Performance Ranking of Automotive Industry Firms in Turkey: Evidence from Entropy Weighted Technique - Bulgurcu, Berna (International Journal of Economics and Financial Issues, 2013)
This paper evaluates the financial performance of the firms in the Turkish automotive industry in the Istanbul Stock Exchange Market (ISEM) by applying the Technique for Order Preference by Similarity to Ideal Solution Methods (TOPSIS). The paper aims to measure and compare the financial performance ranking of these firms. The performances of these firms for a time-period between 2009 and 2012 are assessed and ranked by integrating the TOPSIS method and an entropy-weighted technique that is used to identify the weights of the financial ratios. According to the results, the F-M Izmit Piston firm has the highest performance rate for four years whereas the Parsan firm’s performance index value is the lowest one. Such companies as Ford Auto, Anadolu Isuzu, Ege Industry, Ditas Dogan have stable results for the following four years. This technique, which can also be defined as the Enthropy-Weighted TOPSIS, is understood to be a significant multi-criteria decision-making method in terms of providing objective assessment. Keywords: Financial Ratios; Entropy Technique; the TOPSIS JEL Classifications: G10; M10